A Decade of Progress in Parallel Programming Productivity. - RICHARDS, JOHN T.; BREZIN, JONATHAN; SWART, CALVIN B.; HALVERSON, CHRISTINE A. (Communications of the ACM, 2014)
The article discusses a study that measured programmer productivity starting in 2002 with the U.S. Defense Advanced Research Projects Agency's (DARPA) launched of an initiative in high-productivity computing systems (HPCS). Topics discusses include a comparison between two approaches to parallel programming, the single program multiple data (SPMD) model and the asynchronous partitioned global address space (APGAS) model supported by the X10 language and the time to develop six parallel programs in two languages.